PENGARUH KEPEMILIKAN INSTITUSIONAL, KEPEMILIKAN MANAJERIAL, KOMISARIS INDEPENDEN, LEVERAGE, KOMITE AUDIT DAN UKURAN PERUSAHAAN TERHADAP INTEGRITAS LAPORAN KEUANGAN - Dessy Rina Akhadiani, 13.05.52.0021; Wahyu Widati, Listyorini (Students' Journal of Accounting and Banking, 2017)
This study aims to examine the effects of institutional ownership, managerial ownership, independent commissioners, leverage, audit committees and firm size on the integrity of financial statements. This study focused on LQ45 companies listed in Indonesia Stock Exchange (BEI) period February 2011- January 2016. Research conducted with the number of observations of 126 research samples obtained by nonprobability sampling method is purposive sampling technique. The analysis technique used in this research is multiple linear regression analysis. The results of the analysis show that institutional ownership, independent commissioners, leverage, and firm size have no effect on the integrity of financial statements. Managerial ownership and audit committee influence the integrity of financial statements.Keywords: Institutional Ownership, Managerial Ownership, Independent Commissioner, Leverage, Company Size, Financial Statement Integrity